Research Progress of High Entropy Rare Earth Oxide Thermal Barrier Coating Materials - ZHANG Xiaodong, LIANG Yifan, SONG Yi, WANG Hao, WANG You (Cailiao Baohu, 2024)
Thermal barrier coating (TBC) materials play an important role in protecting the superalloy base from oxidation and corrosion, and reducing the operation temperature of the speralloys in the thermal protection of aero engine and gas turbine. There are many high entropy rare earth oxides in the new thermal barrier coating materials, which can achieve better thermal, mechanical, high-temperature phase stability, sintering resistance, corrosion resistance and other properties than the single principal component rare earth oxides. However, the research on high-entropy rare earth oxides is still in the preliminary stage at present. Especially, the role of rare earth elements on material properties has not been fully defined, and no unified standard has been formed. In this paper, the basic structure of thermal barrier coating was briefly reviewed, and the crystal structure, thermophysical and mechanical properties of five high entropy rare earth salts such as high entropy zirconate, cerate, hafniate, tantalate and niobate were emphatically summarized. In addition, the differences between those salts and the corresponding single component of rare earth salts were compared and analyzed, and many factors affecting their performance were discussed. Compared with single component rare earth oxides, the thermal conductivity, thermal expansion coefficient and phase stability of high entropy rare earth oxides were significantly improved. Finally, the future development direction of high entropy rare earth thermal barrier coatings was prospected.